Strategic planning as a community effort: surveying the perspectives of members of the German Biobank Alliance - Klingler, Corinna; Schiller, Johanna; Huth, Verena; Baber, Ronny; Kirsten, Romy; Specht, Cornelia (Biopreservation and biobanking, 2025)
Background: The German Biobank Node (GBN) coordinates the national network of academic biobanks in Germany; the German Biobank Alliance (GBA). At the beginning of 2025, the GBA consisted of 42 biobanks. With an upcoming strategic reorientation, the GBN/GBA was interested in understanding the perspectives of their community to ensure that strategic decisions were aligned with their needs and interests. - Materials and Methods: An online survey with a cross-sectional design was conducted with the GBA community, targeting mostly first-line management of GBA biobanks. The invitation to the survey was sent via an internal GBA mailing list. It addressed primarily satisfaction with GBN/GBA services, organization of and collaboration within GBN/GBA, and expectations/wishes for the future. Responses were analyzed using descriptive statistics and qualitative content analysis. - Results: Participants generally considered being part of GBA to be important to very important. They emphasized the opportunity to network and exchange with colleagues as particularly helpful, but also training opportunities and quality management (QM) tools provided. In terms of organization, they found that the benefits of cooperating within GBA largely outweighed efforts and that opportunities to participate in processes were adequate. However, they also identified areas for improvement, for example, in the provision of information on how to join or establish working groups. In terms of relevant future topics, participants identified lobbying, networking within and outside GBA, training, and QM as particularly important priorities for GBN/GBA, as well as securing funding and strengthening local cooperation for individual biobanks. - Discussion: The findings have informed the strategic development of GBN/GBA, with QM, education, and networking being the top future priorities. In terms of networking, the GBN/GBA has emphasized the importance of making the perspective of the community heard in other national networks. How to address sustainable funding remains an open question.
Gesehen am 21.10.2025